Akuntabilitas Keuangan Penjualan Madu Kelulut pada Kelompok Tani Natai Kompas di Bawah Binaan Unit Pengelolaan Teknis (UPT) Kesatuan Pengelolaan Hutan (KPH) Wilayah Sintang Timur - Elza Brigitha, Caroline (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2025)
This study aims to analyze financial accountability in stingless bee honey sales managed by the Natai Kompas Farmers’ Group under the supervision of the Technical Management Unit of the Sintang Timur Forest Management Unit (UPT KPH Sintang Timur). This research employs a qualitative descriptive approach using interviews, observations, and financial document analysis. The findings show that the group’s financial recording system is still conducted manually by the treasurer using a ledger to record income, expenses, operational costs, and profit allocation. Although monthly financial reports are prepared and discussed in group meetings, the manual system creates risks of administrative errors, lost transaction evidence, and limited access to financial information for members. The study also finds that member participation in financial decision-making remains limited due to insufficient financial literacy, limited socialization of financial reports, and the absence of a participatory internal control mechanism. To improve transparency and accountability, the study recommends adopting a digital financial recording system, providing financial education and training, increasing access to financial reports, establishing an internal audit team, and encouraging active member participation in financial management.